Antioxidant and Antiatherogenic Responses of Black Solo Garlic in Alloxan-Induced White Rats - saryono, Saryono; Proverawati, Atikah; Jehloh, Latifah (Universitas Jenderal Soedirman, 2023)
The association between the consumption of black solo garlic (SG) and the increase in antioxidant enzymes and the ability to prevent atherogenicity has not been studied much. This study aims to examine the antioxidant and antiatherogenic capacities of black solo garlic in aloksan induced rats. This study used a true experimental design with a pre- and post-test approach with a control group design. The sample of 30 Wistar rats was randomly divided into 6 groups: a healthy control, a negative control, treatment at doses of 6.5, 13.5, and 26 g/KgBW, and positive controls receiving vitamin C at a dose of 1 g/kgBW. The outcomes demonstrated that following the induction, MDA, CRP, LDL, and IL-6 levels increased, while SOD and GSH-Px enzyme levels decreased. After treatment with black solo garlic for 14 days, there was an increase in the enzymes SOD and GSH-Px, as well as a significant decrease in levels of MDA, IL-6, CRP, and LDL in experimental animals. The SG dose of 13.5 g/kg BW is the most effective dose in this study. The active compounds in SG function as antioxidants in preventing atherogenic events.